Kerja Sama Pemerintah Swasta (KPS) Sebagai Upaya Pengembangan Bandar Udara Radin Inten II Lampung Selatan - Dian Sera Fauzela; Bambang Utoyo Sutiyoso; Sasana Putra (Balitbangda Provinsi Lampung, 2019)
Infrastructure availability is one of development priority in developed countries as well as developing countries, including Indonesia. As one of national development priority, budget limitations become a major problem faced by government. Therefore, to resolve budget limitations, government could involve private sector in case of budget funding for infrastructure facilities development. Third party involvement on state achievement known as good governance concept. An effort on third party involvement (private) is known as Public-Private Partnership (PPP). This research chose Radin Inten II Lampung Selatan as the locus. It was chosen because of strategic position and potential passengers on that airport did not directly proportional with infrastructure development efforts. This research has a purpose to understanding priority sequence of Public-Private Partnership form in Radin Inten II Lampung Selatan airport development efforts (air side) and also the most influencing factor on that PPP form. This research was done through descriptive study by using data analysis technique in AHP (Analytical Hierarchy Process) form. The research results show that the most profitable form for air side of Radin Inten II Lampung Selatan airport development is Built Transfer (BT) better than Built-Operate-Transfer (BOT) and Built-Transfer-Operate (BTO). Built Transfer (BT) form selected based on economy criteria (sub criteria: capital), risk criteria (sub criteria: rule of law), and market criteria (sub criteria: demand). From several selected criteria, economy criteria in capital sub criteria was the most influencing factor on PPP form selection.